Metformin‐associated risk of acute dialysis in patients with type 2 diabetes: A nationwide cohort study. Issue 12 (21st September 2016) - Carlson, Nicholas; Hommel, Kristine; Olesen, Jonas B.; Gerds, Thomas A.; Soja, Anne‐Merete; Vilsbøll, Tina; Kamper, Anne‐Lise; Torp‐Pedersen, Christian; Gislason, Gunnar
Abstract : Recent guidelines governing anti‐diabetic medications increasingly advocate metformin as first‐line therapy in all patients with type 2 diabetes. However, metformin could be associated with increased risk of acute kidney injury (AKI), acute dialysis and lactate acidosis in marginal patients. In a retrospective nationwide cohort study, a total of 168 443 drug‐naïve patients with type 2 diabetes ≥50 years, initiating treatment with either metformin or sulphonyl in Denmark between 2000 and 2012 were included in this study (70.7% initiated treatment with metformin); calculation of 1‐year risk of acute dialysis was based on g‐standardization of cause‐specific Cox regression models for acute dialysis, end‐stage renal disease and death. One‐year risks of acute dialysis were 92.4 per 100 000 (95% CI, 67.1‐121.3) and 142.7 per 100 000 (95% CI, 118.3‐168.0) for sulphonylurea and metformin, respectively. The metformin‐associated 1‐year risk of acute dialysis was increased by 50.3 per 100 000 (95% CI, 7.9‐88.6), corresponding to a risk ratio of 1.53 (95% CI, 1.06‐2.23), and a number needed to harm of 1988, thus providing evidence of potential concerns pertaining to the increasing use of metformin.